Preparation of cement spacer in treatment of segmental bone defects in children by the induced membrane technique: A technical note - Pinto, Deepika A. (J Clin Orthop Trauma, 2020)
The Masquelet Induced Membrane Technique (IMT) is one of the tools in the surgeon’s armamentarium for the management of segmental bone defects. The first stage of the IMT includes the insertion of a cement spacer, which is typically fashioned by the free-hand technique. We propose a novel technique for preparation of the cement spacer using a split syringe barrel as a mould. This technique produces a uniformly cylindrical spacer with minimum cement spillage, while also minimizing thermal damage to the surrounding soft tissues. It is a simple and cost-effective method that can be adapted for use in any long bone in children.